Application of GnRH Administration at Post Artificial Insemination in Synchronized Estrus Heifer and Dairy Cows by PGF2α Induction on Conception Rate in Phupan Dairy Co-operative, Sakol-Nakon Province, Thailand - Umpapol, Hanchai; Vajrabukka, Chanvit; Jitrajug, Taradol; Songvicha, Choompol; Tainglum, Surachart; Sirikul, Watchara (Pakistan Journal of Nutrition, 2010)
This experiment was conducted to study the effects of GnRH on conception rate of 32 crossbred Holstein-Friesian dairy cows. All cows were uniform of body condition score and were taken care by the management of small holders in Phupan dairy co-operative, Sakol-Nakon. They were randomly placed in 2 x 2 factorial in randomized complete block design. Factor 1 was for dairy heifers and lactating cows comparison and factor 2 was assigned to compare between distilled water and GnRH injection on day 5 post insemination under the treatments. Blood samples were collected and analyzed for progesterone concentration examination by RIA technique. The environment effects, general physiology and hematology changes were recorded in the entire period of the experiment. The result showed that, the Temperature Humidity Index (THI) was over than 72, which affected the increase of general physiology changes, co-efficient of heat tolerance, sweating rate, hematology and cortisol level concentration that were over standard value. However, there were no significant differences (p>0.05). The examination of serum progesterone concentration on day 11, 17 and 24 post artificial insemination including the conception rate were significantly different (p